Restoring Vitality: The Science and Practice of Pulp Revascularization in Endodontics - Krishna P. Biswas; Dhaval Desai; K Vikram Shetty; Delphia Thomas; Aditi Gupta; Sachin Shashikant Metkari; Rashmi Laddha (Wolters Kluwer Medknow Publications, 2024)
Pulp revascularization is an emerging treatment modality in endodontics aimed at preserving the vitality and function of immature permanent teeth with necrotic pulp and apical periodontitis. This review provides a comprehensive examination of the current state of pulp revascularization, encompassing its rationale, clinical procedures, indications, contraindications, advantages, limitations, and potential future prospects. By critically analyzing the existing literature and clinical experiences, this review aims to offer insights into the efficacy, challenges, and potential advancements in the field of pulp revascularization.